(untitled) (Asian Journal of Social Science Studies, 2016)
The studies of poetic narratology has been extended to the macro-studies of the narrative language of poetic narrative texts ranging from narrative grammar to narrative model with a special attention paid to the exploration of the semiotic atoms of its semantic narration and the semiotic atoms of its pragmatic narration in poetic narrative texts as well as their interrelationships. What hasn’t been paid attention to in this area is the atomic structural system of the semiotic atoms of the narrative signs in poetic narrative texts. Grounded on the absence of studies in this regard, this essay aims to deal with the theoretical construction of the structure of the semiotic atoms of the semantic signs in the narrative language in the narrative poetic texts in terms of the semiotic atoms of the phonetic narration, the semiotic atoms of its semantic narration, the semiotic atoms of its pragmatic narration, the semiotic atoms of its grammatical narration as much as the semiotic atoms of its spatial narration in poetic narrative texts to develop and improve the theories of poetic narratology and expand its studies from macro-studies to micro-studies.